Discriminant analysis and interpretation of nuclear chromatin distribution and coarseness using gray‐level co‐occurrence matrix features for lobular endocervical glandular hyperplasia. Issue 8 (6th May 2020) - Kanai, Ryo; Ohshima, Kengo; Ishii, Keiko; Sonohara, Masaki; Ishikawa, Masahiro; Yamaguchi, Masahiro; Ohtani, Yuhi; Kobayashi, Yukihiro; Ota, Hiroyoshi; Kimura, Fumikazu
Abstract: Background: Lobular endocervical glandular hyperplasia (LEGH) is a disease considered to be the origin of tumorigenesis of minimal deviation adenocarcinoma, which has characteristic expression in the gastric pyloric mucosa. It is difficult to diagnose by nuclear findings because of lower nuclear atypia. In this study, nuclei of endocervical (EC) and LEGH cells were digitized, and nuclear information was quantified from nuclear images and objectively evaluated using a computer. We examined whether it is possible to distinguish between EC and LEGH cells, which is difficult by human eyes. Methods: Signal intensity, morphological features, Otsu thresholding technique and gray‐level co‐occurrence matrix (GLCM) features were calculated from nuclei of EC and LEGH cells on cytology microscopic images. Then, discriminant analysis was performed using the significant difference test and linear support vector machine (LSVM). Results: GLCM features in LEGH cells were higher than those in EC cells. The nuclei of LEGH cells had a higher frequency of signal value pairs with a larger signal value difference than that of EC cells. Therefore, LEGH cell nuclei are thought to have more chromatin granules, and the chromatin is coarse and granular. Moreover, in the LSVM discriminant analysis, the accuracy of GLCM calculated using these features was 85.4%. Conclusion: In this study, GLCM accurately demonstrated the nuclear chromatin distribution and coarseness. Discriminant analysis of EC and LEGH cells using GLCM features is useful.